Changing Influences in Criminology: Examining 45 Years of Criminology Journal Citations. Issue 1 (2nd January 2022) - Barranco, Raymond E.; Perry, Ashley; May, David C.; Stives, Kristen
Abstract: A growing body of research has recently been devoted to quantifying research productivity both on the part of individuals, as well as the prestige that individual productivity levels bring to departments. Only recently has research begun to examine what journals criminologists are most likely to cite in their scholarly research. In this study, we rank the most influential journals cited in Criminology for the years 1969–1973, 1989–1993, and 2009–2013. Our analyses suggest Criminology quickly became the most cited journal, followed by JRCD and Justice Quarterly . Furthermore, the influence of sociological journals has remained strong, but has clearly diminished over time.